Comparing and contrasting responses to tobacco control and obesity policies: a qualitative study. Issue 5 (18th December 2018) - Juszczyk, Dorota; Gillison, Fiona
Abstract: Objective: To explore people's perceptions of, and responses to, obesity and tobacco policies with a particular focus on motivation; and to compare and contrast responses to explore the potential for translating learning across domains. Design: A theoretically informed comparative qualitative study involving semi-structured interviews with two groups of participants (smokers and ex-smokers; those who have previously or are currently attempting to lose weight). Data were analysed inductively using thematic analysis and interpreted through the lens of Self-Determination Theory. Setting: Community-based. Participants: Interviews were conducted with five smokers and four ex-smokers around tobacco policy, and seventeen people acting to control their weight around obesity policy. Results: Three primary themes were identified. (i) Participants believed social norms to be crucial to supporting health behaviour change and responses to policy; not smoking was perceived as socially normal, whereas being physically active and eating healthily were perceived to go against social norms. (ii) Policies influencing the physical environment were perceived to support stopping smoking (e.g. smoke-free laws, advertising bans), but to undermine attempts to lose or control weight (e.g. high visibility, availability and low cost of energy-dense foods). (iii) While policies for both domains were considered necessary and legitimate, both groups found policy interventions neither motivating nor undermining of their sense of autonomy. Conclusions: The results suggest those trying to lose weight respond similarly to obesity-related policy as smokers do to tobacco policy. Environmental interventions are perceived to be more helpful than appealing to people's motivation to change for their own sake.